Erythropoietin enhances hippocampal response during memory retrieval in humans. - Miskowiak, K; O'Sullivan, U; Harmer, C (2007)
Although erythropoietin (Epo) is best known for its effects on erythropoiesis, recent evidence suggests that it also has neurotrophic and neuroprotective properties in animal models of hippocampal function. Such an action in humans would make it an intriguing novel compound for the treatment of neurological and psychiatric disorders. The current study therefore aimed to explore the effects of Epo on neural and behavioral measures of hippocampal function in humans using a functional magnetic resonance imaging paradigm. Volunteers were randomized to receive intravenous injection of Epo (40,000 IU) or saline in a between-subjects, double-blind, randomized design. Neural response during picture encoding and retrieval was tested 1 week later. Epo increased hippocampus response during picture retrieval (n = 11) compared with placebo (n = 12; p = 0.04) independent of changes in hematocrit. This is consistent with upregulation of hippocampal BDNF and neurotrophic actions found in animals and highlights Epo as a promising candidate for treatment of psychiatric disorders.